Individual Prayer in Sumerian: the Continuity of a Tradition - Hallo, William W.
I. A Sumerian Psalter?; II. The Neo-Sumerian Letter-Prayers; III. The Post-Sumerian Penitential Psalms; IV. A New Sumerian Letter-Prayer (H): YBC 4620; YBC 7205; YBC 8630; YBC 4620; YBC 7205; YBC 8630.